Sex-based differences of copeptin for early rule-out of non-ST-elevation myocardial infarction. (25th November 2020) - Vargas, K.G; Tajsic, M; Latsuzbaia, A; Andric, T; Kassem, M; Jaeger, B; Huber, K
Abstract: Objective: There is paucity of data on the role of sex in the dual biomarker strategy using copeptin and conventional troponin for the early rule-out of non-ST-elevation myocardial infarction (NSTEMI). We aimed to evaluate sex-based differences on copeptin levels, combined negative predictive value (NPV) and predictors of copeptin elevation at admission. Methods: Biomarkers were measured in 852 adult patients presenting to the emergency department with chest pain and suspected NSTEMI. Logistic regression analyses on predictors of copeptin elevation were evaluated by sex. Results: Overall, 362 women (42.5%) and 490 men (57.5%) were included. Copeptin levels were higher in men (median 7.36 pmol/L vs. 4.8 pmol/L; P<0.001). Men had a similar NPV (100%) as women (99.6%, CI: 98.8–100) using the dual biomarker rule-out strategy and when compared to troponin alone (men, NPV=98.7%, CI: 97.5–99.8; and women, NPV=98.7%, CI: 97.5–100). Multivariate logistic regression showed positive association of male sex with copeptin elevation (OR=2.37; CI: 1.61–3.49; P<0.001). In men, diastolic blood pressure was a negative predictor of copeptin elevation (OR=0.98, 95% CI: 0.96–0.99), while positive predictors were current MI (OR=2.16, 95% CI: 1.19–3.91), chronic renal insufficiency (OR=3.58, 95% CI: 1.33–9.62), and atrial fibrillation (OR=2.56, 95% CI: 1.23–5.32), respectively (all P<0.05). In women, current MI (OR=2.98, CI: 1.23–7.24), atrial fibrillation (OR=2.90, CI: 1.26–6.70) and syncope (OR=7.56, CI: 2.26–25.30) were significant predictors of copeptin elevation. Conclusions: Men with suspected NSTEMI have higher copeptin levels. The dual biomarker rule-out strategy has a similar performance in both male and female patients. Certain predictors of copeptin elevation are sex-specific. Funding Acknowledgement: Type of funding source: Private grant(s) and/or Sponsorship. Main funding source(s): Ludwig Boltzmann Cluster for Cardiovascular Research, Vienna, Austria